Swarming behaviour in elite race bunch cycling: a case study - Waldron, M.; Worsfold, P.; White, C.; Murray, S. (International Journal of Performance Analysis in Sport, 2011)
The current study undertook a dynamical systems analysis of race bunch cycling, considering the 'sports contest' as a dynamical, self organising system (McGarry et al., 2002). Data from one international track racing event was used to analyse a potential non-linear aggregation theory of 'swarming' in the 'points race', with two objectives; 1) To identify a race profile of a basic swarm mentality within the points race; 2) To identify system stability and the possible perturbation of stability in relation to successful and unsuccessful breakaways. Stability was based upon a 'normal' profile of race behaviours, measured by three separate dependent measures, namely; Absolute Difference, Rate of Change and Phase Duration. Results showed; 1) The points race exhibits the quintessential 'attract and repel' elements that characterise the swarm mentality 2) One-way ANOVA revealed that breakaways of both successful (3.3±1.2 half laps) and unsuccessful (3.1±1.5 half laps) conditions tend to differ from the race 'norm' (2.1±1.3 half laps) in terms of phase duration (F(2, 228)=18.4, P<0.05), suggesting that breakaways perturb the system through longer attract and repel phases. Results are discussed in relation to the current and future effectiveness of describing race bunch cycling as a dynamical system.